Lepidodactylus lugubris (Duméril & Bibron 1836) (Reptilia: Gekkonidae), an introduced lizard new for Brazil, with remarks on and correction of its distribution in the New World - Hoogmoed, Marinus S.; Avila-Pires, Teresa C.s. (Zootaxa, 2015)
Recently seven specimens of the gecko Lepidodactylus lugubris were collected or observed in Belém, Pará, northern Brazil. This is the first vouchered occurrence in Brazil of a widely dispersed (Pacific area) and invasive species (much of the Pacific, parts of northern South America and southern Central America and Florida, U.S.A.). In Suriname the species has already spread into the interior. The distribution of the species is corrected and the history of its introduction in the New World is reconstructed, with an estimation of the state of invasiveness for each country. Some possible routes of introduction are discussed.